Anti-diabetic (AD) and crystal stiffness characterizations of NaBr-added L-alanine (LANB) – A comparative analysis in macro and nano scale crystals. (2020) - Flora, G.; Senthilkannan, K.; Aadhithya Narayanan, S.T.; Senthilkumar, R.
Abstract: LANB crystals are having substantial opto-electronic application, phase matching, frequency matching and power transmission and in natural science as anti-diabetic (AD) and in other utilities. Macro crystals have smallest amount applications by assessment measure up to nano form of LANB. Macro crystals are put in arrayed by slow evaporation solution growth method and nano crystal by ball milling method. LANB are prepared by L Alanine with NaBr 5 h of stirring for 30 days with a, b, c in Å as 6.03, 12.38, 5. 80 and crystals specialty is SHG-NLO. The nano outline of LANB crystals are of 206 nm and 21 nm correspondingly. The toughness, brittleness, Mohs hardness and the yield strength, Young's modulus and stiffness of LANB is also studied and reported here.